GOLPH3 overexpression correlates with poor response to neoadjuvant therapy and prognosis in locally advanced rectal cancer - Zhu, Kunli (Oncotarget, 2016)
Neoadjuvant chemoradiotherapy (nCRT) combined with surgery is a standard therapy for locally advanced rectal cancer (LARC). The aim of this study was to assess the expression of GOLPH3 (Golgi phosphoprotein 3), a newly found oncogene, in LARC as well as its relationship with nCRT sensitivity and prognosis. We retrospectively analyzed 148 LARC cases receiving nCRT and total mesorectal excision (TME). Immunohistochemistry was used to assess GOLPH3 and mTOR (mammalian target of rapamycin) in tumor tissues. Then, the associations of GOLPH3 with pathological characteristics and prognosis of rectal cancer were assessed. The 148 cases included 77 with high GOLPH3 expression (52.03%), which was associated with tumor invasive depth and lymphatic metastasis. Cases with high GOLPH3 expression had 2.58 and 2.71 fold higher local relapse and distant metastasis rates compared with the low expression group. Correlation analyses showed that GOLPH3 was an independent indicator for judging tumor down-staging and postoperative TRG (tumor regression grade), indicating it could predict nCRT sensitivity. In addition, GOLPH3 expression was associated with mTOR levels. Multiple-factor analysis indicated that GOLPH3 was an independent prognosis indicator for 5 year-DFS (disease free survival) and OS (overall survival) in LARC. These results reveal that GOLPH3 is an independent predictive factor for nCRT sensitivity and prognosis in LARC, with a mechanism related to mTOR.